DO EQUAL OPPORTUNITIES FOR RURAL MULTI-GRADE LEARNERS EXIST? - Gawie Schlebusch (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This paper explores the distinctive challenges of teaching and learning in multi-grade classrooms in rural areas of the Free State Province, South Africa. It seeks to identify effective strategies suited to the unique needs of learners in these contexts. The qualitative study involved 14 Intermediate Phase teachers and 6 principals from multi-grade schools in the Lejweleputswa and Fezile Dabi districts, selected through purposive sampling. Data were gathered using semi-structured interviews and analysed thematically through an interpretive qualitative approach. Findings reveal that teaching strategies in multi-grade classrooms are diverse, influenced by teacher personality, subject content, and classroom dynamics. These approaches also reflect the teacher’s skills, the lesson objectives, and the physical constraints of the classroom space. Despite this diversity, both teachers and principals reported insufficient training or orientation in approaches specifically designed for multi-grade teaching. This lack of targeted preparation raises critical questions about whether learners in rural multi-grade schools are afforded equal opportunities to achieve academic success compared to their peers in more conventional school settings.